The Ross–Konno operation for neonates and infants with severe aortic incompetence following treatment for critical aortic stenosis. (3rd July 2021) - Hebala, Muhammed; Rao, Vinay; Jaber, Osama; Congiu, Stefano; Bentham, Jamie; Thomson, John; van Doorn, Carin
Abstract:  : OBJECTIVES: Aortic valve stenosis in neonates and infants is associated with congestive cardiac failure, and balloon or surgical valvuloplasty provides relief of stenosis. Occasionally severe aortic insufficiency necessitates urgent aortic valve replacement. We reviewed our experience with the Ross–Konno procedure in patients <1 year. METHODS: Between October 2013 and May 2020, 36 patients underwent balloon (34) or surgical (2) aortic valvuloplasty for aortic stenosis. Six patients subsequently underwent a Ross–Konno procedure. The median age at operation was 55 (27–116) days and weight was 4.25 (2.5–12) kg. All patients were in severe cardiac failure and had a small aortic annulus with Z -score −3.1 (−1 to −4.4). RESULTS: There were no early or late deaths. At the latest follow-up at 39 (13–60) months, ventricular function had improved in all patients and no patient was on anti-failure medication. On echocardiography, there wasno more than trivial aortic regurgitation and no left ventricular outflow tract obstruction. One patient required right ventricle to pulmonary artery conduit replacement and one patient had homograft stenting. CONCLUSIONS: Despite the severe preoperative haemodynamic compromise, the urgent Ross–Konno procedure was associated with excellent operative survival and recovery of ventricular function. The need for reintervention to the pulmonary conduit remains a cause for concern.